Epistemological Transformation of ʿUrf in the DSN-MUI Fatwa on E-Commerce: A Maqāṣid al-Sharīʿah Based Analysis - Sanuri; Mubarok, Nafi'; Musafa’ah, Suqiyah; Irama, Yoga (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2025)
The rapid growth of digital platforms in global commerce has reshaped conventional transactional norms, including among Indonesian Muslims, raising normative debates on the legitimacy of e-commerce within Islamic jurisprudence. While prior studies have addressed e-commerce in Islamic legal discourse, few have examined the transformation of ʿurf (customary practice) as a legitimate legal source in the digital age. This study introduces the DigitalʿUrf Alignment Model (DUAM), an integrative legal-epistemological framework that systematizes the adaptation of classical ʿurf to digital contexts through maqāṣid al-sharīʿah based validation. Employing a qualitative-normative approach, the research analyzes Fatwa No. 146/2021, issued by the National Sharia Council of the Indonesian Ulema Council (DSN-MUI), classical and contemporary fiqh sources, and emerging digital transaction models. It integrates concepts from uṣūl al-fiqh, maqāṣid al-sharī‘ah, and socio-philosophical reasoning to reconceptualize ʿurf as a dynamic category of legal interpretation. The findings affirm that digital ʿurf, structured through DUAM, enables its institutionalization as a normative legal source for fatwa and provides a scalable method for integrating classical jurisprudence with digital finance regulations.